1990
DOI: 10.3181/00379727-194-43046
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins as Mediators of Acidification in the Urinary Bladder of Bufo marinus

Abstract: Experiments were performed to determine whether prostaglandins (PG) play a role in H+ and NH4+ excretion in the urinary bladder of Bufo marinus. Ten paired hemibladders from normal toads were mounted in chambers. One was control and the other hemibladder received PGE2 in the serosal medium (10(-5) M). H+ excretion was measured by change in pH in the mucosal fluid and reported in units of nmol (100 mg tissue)-1 (min)-1. NH4+ excretion was measured colorimetrically and reported in the same units. The control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…In both toad bladder [106,107] and rat kidney [108], prostaglandin E 2 levels have been shown to increase in response to chronic metabolic acidosis, leading to enhanced proton excretion rates. The acidosis-induced inhibition of the hydroosmotic response to vasopressin in the toad bladder is also apparently mediated by increased prostaglandin E 2 synthesis.…”
Section: Role Of Prostaglandin Productionmentioning
confidence: 98%
“…In both toad bladder [106,107] and rat kidney [108], prostaglandin E 2 levels have been shown to increase in response to chronic metabolic acidosis, leading to enhanced proton excretion rates. The acidosis-induced inhibition of the hydroosmotic response to vasopressin in the toad bladder is also apparently mediated by increased prostaglandin E 2 synthesis.…”
Section: Role Of Prostaglandin Productionmentioning
confidence: 98%
“…These structurally different compounds produced similar effects whereas the inactive epimer of phorbol 12-myristate 13-acetate was without an effect. In toad urinary bladder, however, enhanced acidification was seen with the nonphorbol PKC activator mezerein (70). A summary of the effects of activating PKC on ion transport processes is presented in Table 111.…”
Section: Phospholipids As a Source Of Second Messengers In Ion Transpmentioning
confidence: 96%
“…In nonosseus cells, metabolic acidosis increases the levels of prostaglandins (1,34,35,41). In both toad bladder (34,35) and rat kidney (41), PGE 2 levels have been shown to increase in response to metabolic acidosis.…”
mentioning
confidence: 99%
“…In the brains of newborn pigs, acidosis increases the level of prostaglandins that are associated with vasodilatation (1). An increase in prostaglandin levels by bone cells is important as prostaglandins are potent local stimulators of bone resorption and appear to mediate resorption induced by a variety of cytokines and growth factors (35,62). Goldhaber and Rabadjija (40) first demonstrated that the prostaglandin inhibitor indomethacin inhibits acid-induced, cell-mediated calcium efflux from bone, and Rabadjija et al (61) subsequently demonstrated that protons stimulate release of PGE 2 from neonatal mouse calvariae.…”
mentioning
confidence: 99%
See 1 more Smart Citation